Cycling Cities as a Government Effort to Realize Sustainable Cities in Yogyakarta in 2023-2024 - Regina Azzahra Mahabatan; Muhammad Eko Atmojo (ARISTO, 2026)
The growth in the number of vehicles in Yogyakarta has contributed to increased air pollution, despite a significant decline during the COVID-19 pandemic. To mitigate these environmental impacts, the government is promoting a bicycle-friendly city program, but its effectiveness still requires support in the form of adequate facilities, strong regulations, and public awareness of cycling. This study was conducted using a qualitative descriptive method that combined literature review, interviews, and field observations as triangulation techniques. This approach aimed to obtain an in-depth picture of the implementation of bicycle-friendly city policies in Yogyakarta and the obstacles that arose in their implementation. The results show that the development of bicycle lanes not only supports environmentally friendly mobility but also encourages local economic growth. From an economic perspective, the existence of bicycle lanes not only facilitates environmentally friendly mobility but also encourages local economic growth through bicycle-based tourism, sporting events, and the empowerment of MSMEs. From an environmental perspective, the construction of bicycle lanes is in line with air pollution control, noise reduction, and the development of green open spaces that continue to pay attention to ecosystem sustainability and support climate change mitigation. Meanwhile, from a social perspective, the government has implemented various educational programs and cycling campaigns from an early age to the public, which are reinforced by the development of supporting infrastructure such as special lanes, traffic signs, and bicycle parking. Overall, community involvement is an important factor in supporting this policy because its success depends not only on regulations but also on the collective awareness of citizens. This policy demonstrates the integrated efforts of the Yogyakarta City government in creating a sustainable, inclusive Cycling City that supports the welfare of the community